HARMONIC RESPONSE EVALUATION OF FRAME-TYPED MACHINERY FOUNDATION USING FIXED-END SUPPORTS AND SOIL-STRUCTURE INTERACTION - Muhammad Immaduddin; Hidayat Soegihardjo M.; Ananta Sigit Sidharta (Institut Teknologi Sepuluh Nopember, 2009)
It has been generally recognized that the interaction between soil and structure can indeed affect the response of structure, especially for those structures founded on relatively flexible soil. Flexibility foundation caused by soil movement below, often becomes important factor in structural design and it will give more useful and realistic model. Therefore, the inclusion of soil-structure interaction (SSI) effect is particularly important in the analysis of structures subject to dynamic loads. A structures of Framed type machinery foundation structure built on soft clay was used as a model. It’s response was compared to fixed-base model in order to find-out the fixed-base condition model, in which it gave a result that was closed to SSI result responses that considering soil-structure interaction effect could be analyzed using fixed-base model. The condition was reached on model with length-height ratio of frame has non linear relation to beam-column stiffness ratio but it was almost liniear with gradient -1.13 on semi logarithmic scale.